Ciało – obce, sprawcze, kreatywne. O doświadczaniu laryngektomii - Biernacka-Gemel, Adrianna; Zieliński, Konrad (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2022)
The purpose of this article is to elaborate a holistic anthropological approach to the experience of people who have had laryngectomy (surgical voice box removal). While most humanistic approaches to illness and disability focus either on power relations, social constructions or individual subject’s experience, we propose to dive deep into the bodily reality of laryngectomy, investigating physiological adaptations to the changed anatomy, development of new habits and interactive behavior patterns. The linkage between body and more typical anthropological concerns – namely social practices and self-narratives – is developed using new materialism and enactivism as theoretical bases. In result, we demonstrate remarkable creativity of body-self that can be traced at every level of embodiment (from organic processes to storytelling).
il. ; 24 cm
Keywords: etnografia -- czasopisma; laryngectomy; embodiment; medical anthropology; disability; enactivism; new materialism; body; communication